2017
DOI: 10.21608/ejars.2017.6823
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Historical Bookbinding Leather by Ftir,sem -Edx and Investigation of Fungal Species Isolated From the Leather

Abstract: The aim of the present study was to identify fungi that cause deterioration of historical leather in the storage room, compare quantitative compounds of elements present in historical leather and new ones, and check the ability of the isolated fungi from recently leather book to colonize new leather. The leather binding was evaluated by visual assessment, SEM, isolation and identification of fungi and Fourier Transform Infrared Spectroscopy (FTIR). Goat skin was identified as the animal skin of the bookbinding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…In recent decades, a challenge has emerged for restorers, architects and researchers on the development of appropriate treatments for contaminated objects and the prevention of fungal growth. Fungi can inhabit, alter and degrade all types of organic and inorganic materials [26]. The inactivation of fungal and bacterial species by ultra-violet radiation (UV) has been known for a long time [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent decades, a challenge has emerged for restorers, architects and researchers on the development of appropriate treatments for contaminated objects and the prevention of fungal growth. Fungi can inhabit, alter and degrade all types of organic and inorganic materials [26]. The inactivation of fungal and bacterial species by ultra-violet radiation (UV) has been known for a long time [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors reported that the most common fungal strains isolated from historical papers were A. flavus and A. niger, whereas the fungal strains A. terreus, A. niger, and A. flavus were the most common strains isolated from leather bookbinding. Mansour et al reported that the fungal strains Cladosporium cladosporioides, Eurotium chevalieri, Fusarium poae, Wallemia sebi, A. fumigatus, and A. tamarii were the most common fungi isolated from leather bookbinding dating back to 18th century [41].…”
Section: Fungal Isolation and Identificationmentioning
confidence: 99%